Digital communication in social networks and user interaction - Argota-Pérez, Geomanis (2024)
Digital communication is based on the convergence of technological advancements and communicative practices in digital environments, enabling data exchange across various electronic devices. Additionally, it stands out for its interactivity and ability to overcome limitations of time and space, facilitating instant and global connections. The objective was to analyze digital communication on social media and user interaction. It is described that access, inclusion, and digital literacy are essential concepts for democratizing information. On social media, users interact to share ideas and content. Disruptive marketing strategies are recognized towards the migration of digital channels like social media. The effectiveness of marketing on social media influences brand value and business competitiveness. Social media platforms are vital for establishing relationships with customers and dispelling doubts that may affect online purchases. The strategic use of social media to interact among and with customers enhances perception and promotes more authentic and close communication, while user-generated content redefines communication dynamics by fostering diversity of perspectives and experiences.